2008
DOI: 10.1007/s00167-008-0686-8
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff tears: pathology and repair

Abstract: By virtue of its anatomy and function, the rotator cuff is vulnerable to considerable morbidity, often necessitating surgical intervention. The factors contributing to cuff disease can be divided into those extrinsic to the rotator cuff (most notably impingement) and those intrinsic to the cuff (age-related degeneration, hypovascularity and inflammation amongst others). In an era of emerging biologic interventions, our interventions are increasingly being modulated by our understanding of these core processes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 101 publications
2
39
0
2
Order By: Relevance
“…Acromial morphology in particular contributes to bursal sided cuff tears. 19 More commonly, cuff tears are thought to begin on the articular side in the context of age-related degeneration and microtrauma. 19 Inflammatory changes, oxidative stress, tissue remodeling and apoptosis are all important parts of this pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…Acromial morphology in particular contributes to bursal sided cuff tears. 19 More commonly, cuff tears are thought to begin on the articular side in the context of age-related degeneration and microtrauma. 19 Inflammatory changes, oxidative stress, tissue remodeling and apoptosis are all important parts of this pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…Extrinsic factors include repetitive impingement under the acromion, whereas intrinsic factors are defined by a degeneration-microtrauma model. 27 The degeneration-microtrauma model likely explains GTPS pain because abnormalities around the greater trochanter, such as osteophytes or calcifications, are seen in 40% of patients. 5 Changes within the gluteal tendons have been confirmed by several recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…49 The increased prevalence of tears over time, the common finding of an increase in tear size, and the worsening of the muscle functional capacity with progressive atrophy and fatty infiltration have led some surgeons to believe that rotator cuff tears should be repaired early in their course. 24,66 Ellman et al 22 showed poorer results with surgery with increased preoperative weakness of the shoulder, less active range of motion, and narrowing of the acromiohumeral distance suggestive of a larger tear. Burkhart et al, 11 while finding that patients with advanced fatty infiltration of the cuff muscles can often benefit from rotator cuff repair, also found that the improvement was not nearly as good in the patients with more advanced fatty infiltration.…”
Section: Anatomymentioning
confidence: 97%